(untitled) (International journal of artificial intelligence, 2025)
This thesis provides an in-depth analysis of the role of young leaders in the modern management system, their psychological and social characteristics. The ability of young leaders to make decisions, communicate with the team, resolve conflicts, and think innovatively is studied in their personal qualities and interactions with the social environment. The study highlights the management style, leadership model, level of responsibility, and initiative of the new generation of leaders, which are being formed in accordance with the requirements of the current era, based on psychological analysis. It also examines the impact of young leaders on the effectiveness of the organization through their trust in the team, motivation, and communication skills.